Első lépések egy alternatív tudatfelfogás felé - Ertüngealp, Alpaslan (Kultúratudományi Szemle, 2024)
First steps towards an alternative understanding of consciousness In some languages the distinction between mind and consciousness (and the synonymizing of the two) is not simply a matter of linguistic tradition and convention; the difference between the two can be explored through metaphysical arguments on the one hand, and physicalist/neuroscientific approaches on the other (psychology cannot be neglected from general research but must be omitted for a purely philosophical approach). In this paper, I explore the difference between the two by supporting or refuting contemporary conceptions of consciousness with the help of Kantian transcendental theories and propose that consciousness is a static mental structure that allows the use of conscious as an attribute when certain mental phenomena and actions find their place in the structure of consciousness. To this (in line with modular mind theories) I associate a physicalist proposal that brain networks, neuronal groupings (not hierarchically) can form a network of “consciousness” through lending particular parts of their networks. Moving forward from there, I explore the possibilities for the emergence of self-consciousness and propose that self-consciousness is a type of conscious mental actions and cannot be a mental structure. In this paper, I also analyze the debate on the unity of experience (the experiential part [Bayne and Chalmers] and the non-experiential part [Tye and Searle] views) and attempt to bridge the two views.